2006
DOI: 10.1161/01.str.0000196989.09900.f8
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage Associated With Oral Anticoagulant Therapy

Abstract: Background and Purpose-Life-threatening intracranial hemorrhage, predominantly intracerebral hemorrhage (ICH), is the most serious complication of oral anticoagulant therapy (OAT), with mortality in excess of 50%. Early intervention focuses on rapid correction of coagulopathy in order to prevent continued bleeding. Summary of Review-This article reviews the epidemiology of OAT-associated ICH (OAT-ICH), and current treatment options, with the aim of providing a framework for future studies of unresolved questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
203
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(221 citation statements)
references
References 84 publications
5
203
1
12
Order By: Relevance
“…In the 15 of these patients who also received PCC, the dose of FFP was 1-2 units, as specified by the protocol (when given with PCC). However, in the remaining patients (FFP and vitamin K alone), doses of FFP were also small (median 2 units, range [1][2][3][4][5][6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 15 of these patients who also received PCC, the dose of FFP was 1-2 units, as specified by the protocol (when given with PCC). However, in the remaining patients (FFP and vitamin K alone), doses of FFP were also small (median 2 units, range [1][2][3][4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for effective options to ameliorate these poor outcomes is lacking, and there is only modest consensus on the best acute management strategies. 1,5 Estimates of WRICH frequency vary between 6% and 24% of all intracerebral haemorrhages (ICH). 3,[5][6][7] Higher international normalised ratios (INR) have a higher risk of WRICH, but most WRICH occur at an INR within the target therapeutic range.…”
Section: Introductionmentioning
confidence: 99%
“…with anticoagulation-associated ICH (Steiner et al, 2006). With regard to antiplatelet pretreatment, clinical studies revealed much more controversial results (Wijman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase is most likely due to the increased use of warfarin by patients with atrial fibrillation [58]. The use of warfarin at the time of ICH is associated with hematoma expansion [16,18] and increased mortality [15][16][17]59].…”
Section: Anticoagulation Reversalmentioning
confidence: 99%